Review of childhood genetic nephrolithiasis and nephrocalcinosis - Gefen, Ashley M.; Zaritsky, Joshua J. (Frontiers in Genetics, 2024)
Nephrolithiasis (NL) is a common condition worldwide. The incidence of NL and nephrocalcinosis (NC) has been increasing, along with their associated morbidity and economic burden. The etiology of NL and NC is multifactorial and includes both environmental components and genetic components, with multiple studies showing high heritability. Causative gene variants have been detected in up to 32% of children with NL and NC. Children with NL and NC are genotypically heterogenous, but often phenotypically relatively homogenous, and there are subsequently little data on the predictors of genetic childhood NL and NC. Most genetic diseases associated with NL and NC are secondary to hypercalciuria, including those secondary to hypercalcemia, renal phosphate wasting, renal magnesium wasting, distal renal tubular acidosis (RTA), proximal tubulopathies, mixed or variable tubulopathies, Bartter syndrome, hyperaldosteronism and pseudohyperaldosteronism, and hyperparathyroidism and hypoparathyroidism. The remaining minority of genetic diseases associated with NL and NC are secondary to hyperoxaluria, cystinuria, hyperuricosuria, xanthinuria, other metabolic disorders, and multifactorial etiologies. Genome-wide association studies (GWAS) in adults have identified multiple polygenic traits associated with NL and NC, often involving genes that are involved in calcium, phosphorus, magnesium, and vitamin D homeostasis. Compared to adults, there is a relative paucity of studies in children with NL and NC. This review aims to focus on the genetic component of NL and NC in children.